Production of trivalent influenza vaccines: disposable technology and insect cell lines - Woolley, Andrew W. (Kansas State University. K-State Libraries, 2014)
The overall production for the entire process is 22 million doses per year. This production capacity is approximately the same as a medium sized facility. Using a baculovirus insect cell expression system can reduce the production time of influenza vaccines from 6 months to 4 months. The other cell line considered, Chinese Hamster Ovaries, was determined to be unfavorable due to safety concerns. It was determined that disposable technology would be ideal for the process, as it allows production scale up with minimal capital investment. The disposable technology employed in the facility was found to be more economically viable than conventional multi-use technology. The facility still requires the use of some multi-use components, such as chromatography and diafiltration, but single use technology is employed where possible. Examining the project, a lifespan of 23 years was determined to be appropriate for demonstrating the economic feasibility of the project. It was found that the minimum IRR at current prices was 33.36%. With a 12% discrete interest rate, the net present value of the facility is $278 million, for a total capital investment of $149 million. At this rate, it was also determined that the payback period was 2.83 years with a return on investment of 34.42%. From this data, it was concluded that the project should proceed as planned.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Citation: Woolley, A. (2014) Production of trivalent influenza vaccines: disposable technology and insect cell lines. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Trivalent; Influenza; Vaccine; Facility; Disposable; Insect